Lymph Node Transplantation and Its Immunological Significance in Animal Models - Manuela Buettner; Ulrike Bode (Clinical and Developmental Immunology, 2011)
Lymph nodes (LNs) are distributed all over the body and whatever the site consists of the same cell populations. However, there are great differences between LN from different draining areas. For example, in mesenteric LN, homing molecules, for example, CCR9 and α4β7 integrin, were induced and cytokines, for example, IL-4, were produced on higher levels compared to peripheral LN. To study the immunological functions of LN, LN transplantation was performed in some specific areas using different animal models. Many groups investigated not only the regeneration of transplanted LN but also the induction of immune responses or tolerance after transplantation. Existing differences between LNs were still detectable after transplantation. Most important, stromal cells of the LN were identified as responsible for these differences. They survive during regeneration and were shown to reconstruct not only the structure of the new LN but also the microenvironment.